COMPLEX PROCESSING OF SILUMINS WITH DISPERSE PARTICLES AND ATOMIC NITROGEN - A. T. Volochko; A. Ju. Izobello; V. V. Ovchinnikov (Литьë и металлургия, 2009)
The investigations on production of composite materials on the basis of the treated by dispersed particles and atomic oxygen are presented.